Extent of Implementation of a Formal Ethical Code of Conduct: Basis for Crafting an Intervention Program in Oras Accounting Services: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ms. Karen Ronsayro was operating as a sole proprietor in 2014 at Coruna Street Village EastCainta Rizal and offered accounting services. Yet, not everything functions perfectly. In 2019,Ms. Ronsayro and her father, Mr. Rey Osea, founded ORAS Accounting Services at 4 LawinStreet in Novaville, Caloocan City. The company changed its name to Osea RonsayroAccounting Services and started providing auditing, tax filing, registration or permit, andbookkeeping services. Orientation, observation, demonstration, training, and applicationsystems are used for their training system. They carry out the tasks assigned to them. Anaccounting staff member needs to possess certain qualities, including integrity, honesty, anddependability. Professionalism and confidentiality should also be top priorities. This study wasdesigned to assist in developing an intervention program by extending and putting intopractice a formal ethical code of conduct. This study aims to evaluate the effectiveness of anintervention program at ORAS Accounting Services in producing employees who areprogressive and fit to work for a certain job or career as a result.This study revealed that there is no significant difference between the assessment of Maleand Female groups of respondents in the Extent of Implementation of a Formal Ethical Codeof Conduct in terms of rules, expectations and management, company policies to helpcompliance, Guidelines for Behavior, and Day-to-day business practices. This was confirmedby the t-computed value of 1.0730, which is less than the t-critical value of 3.707 at 0.01 levelof significance and 6 degrees of freedom. With these compared values, the null hypothesis isAccepted.The Proposed Intervention Program includes the key Result Area on rules expectation andmanagement, company policies to help compliance, Guidelines for Behavior, and Day-to-daybusiness practices. Other areas included in the intervention program were as follows:Objective, Program of Activity, Person Involved, Time Frame, Budget, Monitoring, andEvaluation.
Keywords: Business